Silicon high performance devices using subwavelength structures - Halir, Robert; Sánchez-Postigo, Alejandro; Luque-González, José Manuel; Herrero-Bermello, Alaine; Leuermann, Jonas; Ortega-Moñux, Alejandro; Wanguemert-Pérez, Juan Gonzalo; Velasco, Aitor V.; De-Oliva-Rubio, José; Schmid, Jens H.; Cheben, Pavel; Soler-Penades, Jordi; et al. (My University, 2019)
Silicon photonics is poised to solve challenges in areas such as datacom, environmental monitoring and diagnostics, by leveraging the economies of scale afforded by CMOS manufacturing. This requires a wide variety of integrated silicon devices, including fiber-to-chip couplers, polarization splitters and waveguide couplers, operating both in the near-infrared and the mid-infrared wavelength range. However, the reduced set of materials available in this platform can often limit the performance of these devices. Subwavelength structures enable the synthesis of optical metamaterials, with properties than can be tuned to enhance device performance, by using fully etched silicon structures with a periodicity smaller than the wavelength of light. Here we review the basic operating principles of these structures, discuss how to efficiently model them, and report on the latest advances in this rapidly growing field.
Ministerio de Economía y Competitividad, Programa Estatal de Investigación, Desarrollo e Innovación Orientada a los Retos de la Sociedad (cofinanciado FEDER), Proyecto TEC2016-80718-R Universidad de Mälaga
Keywords: Fotónica - Materiales; Subwavelength structures; Silicon photonics